THE FIXED DETERMINANT UPDATE FOR UNCONSTRAINED OPTIMIZATION - Mahmood, Saad Shakir; Mansour, Ali Ibrahem (MAGISTRA, 2010)
In this paper, we proposed a new method to compute the LU factors for Hessian matrix, for an update if it its determinant known. Numerical examples are given at the end of this paper.